Apply the Precautionary Principle Concerning Combined Hormonal Contraception Use in Adolescents. Issue 2 (3rd May 2016) - Prior, Jerilynn C.
Abstract : Here I respond to Akers, Dhar, and Shah's (2016), Stubbs's (2016), Olshansky's (2016), and Kissling's (2016) commentaries on the article (Prior, 2016) in which I expressed concerns about the potential adverse long-term reproductive and bone health effects on normal adolescents' maturation related to use of combined hormonal contraceptives (CHC) for contraception and/or treatment. Although Akers et al. (2016) take exception, the precautionary principle on which medical/pharmaceutical ethics is based challenges us to show that CHC is officially indicated and effective in randomized, double-blind, placebo-controlled trials with adolescents. Those who support current practices are obligated to provide young patients and their parents with evidence from large, population-based, prospective studies (or meta-analyses of longitudinal data) that adolescents who have used CHC develop the same menstrual cycle/ovulatory function, fertility, and reproductive lifespan and similar bone density and strength as peers who did not use CHC. Without this information there can be neither reproductive justice (Kissing, 2016), nor true choice. Why is this minimal, expected scientific data not available? It is likely that authors of practice guidelines for adolescent CHC contraceptive use and who advocate its "non-contraceptive benefits" have pro-estrogen cultural biases or conflicts of interests due to pharmaceutical industry connections. I agree with Olshansky (2016) that we should listen to adolescents' concerns and use evidence-based and safe treatments for milder heavy bleeding and cramps. For heterosexual adolescents seeking contraception, we can suggest and explain the use of safer, yet effective, nonhormonal strategies, such as the copper IUD or a barrier plus full-dose vaginal spermicide.